### Need help from an expert?

The world’s top online tutoring provider trusted by students, parents, and schools globally.

To integrate (x+1)^2/(x^2+1), use partial fractions and substitution.

First, use partial fractions to break up the integrand into simpler fractions:

(x+1)^2/(x^2+1) = A(x+1)/(x^2+1) + B(x+1)^2/(x^2+1)^2

To find A and B, multiply both sides by the denominator and simplify:

(x+1)^2 = A(x^2+1) + B(x+1)^2

Expanding and equating coefficients, we get:

A+B = 1

2B = 1

Therefore, A = 1/2 and B = 1/2.

Substitute u = x^2+1 and du = 2x dx to simplify the integral:

∫(x+1)^2/(x^2+1) dx = ∫(1/2)(x+1)/(x^2+1) dx + ∫(1/2)(x+1)^2/(x^2+1)^2 dx

= (1/2)ln(x^2+1) + ∫(1/2)(1+2x^2+2x)/(x^2+1)^2 dx

= (1/2)ln(x^2+1) + ∫(1/2)(1/(x^2+1)^2) dx + ∫(x/(x^2+1)^2) dx + ∫(x/(x^2+1)^2) dx

= (1/2)ln(x^2+1) + (1/2)arctan(x) - (1/2)(1/(x^2+1)) + (1/2)(1/(x^2+1)) + C

= (1/2)ln(x^2+1) + (1/2)arctan(x) + C

Therefore, the integral of (x+1)^2/(x^2+1) is (1/2)ln(x^2+1) + (1/2)arctan(x) + C.

Study and Practice for Free

Trusted by 100,000+ Students Worldwide

Achieve Top Grades in your Exams with our Free Resources.

Practice Questions, Study Notes, and Past Exam Papers for all Subjects!

The world’s top online tutoring provider trusted by students, parents, and schools globally.

Loading...

Loading...